Pengembangan Assessment Untuk Mengukur Kemampuan Problem Solving Materi Interaksi Makhluk Hidup Dengan Lingkungan - Abdul Aziz; Ahmad Walid; Istiana Alfarisi (-)
Assessment can be interpreted as the process to obtain information in any form that can be used for the basis of decision making about students, whether it concerns the curriculum, learning programs, school climate or school policies. This research aims to know how the form and feasibility of assessment to measure the ability of problem solving in the material interaction of living beings with the environment in junior high school in Bengkulu. The type of research used is Research and Development. The development model used is the Borg and Gall models adapted by Sugiyono with 8 stages. Based on the results of expert validation obtained expert assessment score of 88.20%, material expert score of 86.14, linguist score of 88.25%. Based on the results of research in junior high schools in Bengkulu, there are 13 valid questions, SMP B has 13 valid questions, SMP C has 14 valid questions, while the reliability of junior high schools in Bengkulu get good criteria, while the different power of junior high schools in Bengkulu gets 4 groups of items, with categories very difficult, difficult, easy and very easy. while the difficulty level of SMP A item category problem is very difficult there is 1 item, difficult 9 items, easy 3 items, and very easy 2 items. While SMP B category item problem is very difficult there is 1 item, difficult 9 items, easy 1 item and very easy 3 items, while SMP C category item problem is very difficult there is 1 item, difficult there are 8 items, easy there are 4 items and very easy 2 items. While the person fit order from SMP A fit, SMP B there is 1 misfit and SMP C 3 there is misfit.